Attracting the Foreign Direct Investment (FDI) Using Financial Network: A Case in Zimbabwe - Masango Matimura; Colin Gan Cheong Kiat; Raden Aswin Rahadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2021)
The purpose of this study is to investigate the critical reasoning and to develop a research framework on how to attract foreign direct investment (FDI) to rebuild the country from the economic slump caused by previous government failure. By applying a trusted financial network such as Sardex, business owners would be able to access FDI. By applying performance metrics based on The Morgan Stanley Capital International – Environmental, Social, and Governance or MSCI-ESG risk factors and principles of responsible investment, the study can measure the efficiency and the productivity of the proposed financial network. Experiments will be carried out to determine how efficient and productive ZimNet is in assisting Zimbabwe to attract FDI. This research is one of the first studies investigating the critical reasoning and developing a research framework on attracting FDI for the country's economic rebuilding. This study would also be the first to measure the efficiency and productivity of the proposed financial network.